A comparison of student attitudes toward physical activity in a traditional and block scheduled physical education curriculum in four Wisconsin high schools - Halverson, Kara S. (My University, 2002)
This study was designed to determine the impact of traditional versus block scheduling of physical education on high school students' attitudes toward physical activity. The subjects surveyed were Wisconsin public high school students (N = 487) enrolled in physical education. The sample included 2 schools from a block schedule (n = 174) and 2 schools from a traditional schedule (n = 3 U),w hich consisted of a total of 253 males and 234 females. The questionnaire consisted of 6 demographic variables, 26 five-point Likert-type scale statements, and 8 open-ended questions. Subjects completed the questionnaire to examine current attitudes about student experiences in physical education, choices offered in the physical education curriculum, and the expectations students had for their participation in physical activity. Mean scores in relation to attitudes toward activity were 3.852 for males and 3.709 for females. Mean scores were found not to be statistically different. Results of a two-wav ANOVA indicated no significant difference @ = .916) between the traditional a d block scheduled program. However, the results indicated a significant difference @ = .001) between males and females involved in a traditional and block scheduled physical education program.
Keywords: High school students - Wisconsin - Attitudes; Physical education and training - Curricula; Physical education and training --Study and teaching (Secondary) - Wisconsin; Block scheduling (Education) - Public opinion